A Project development and management study on e-light Company - Mendoza, Lloren S.; Olpindo, Vanessa T.; Parreno, Kristina E. (Diliman, Quezon City College of Engineering, 2001)
With the government's campaign for energy efficient lighting, the Department of Energy-Fuels and Appliance Testing Laboratory aims to know the feasibility of converting the majority of the Incandescent Lamp, IL, users to Compact Fluorescent Lamp, CFLs, users. From a market study conducted by the Arthur Andersen, it was found out that one of the major reasons why ILs are still largely used is the high cost of CFLs. From this premise the group conducted a feasibility study on manufacturing a less expensive but of high quality CFLs. To determine if there really is a demand for the product, the study began with the Market Study; the product and its properties are determined. The product is a compact fluorescent lamp with the property of a high-cost CFL that is out in the market, but with a significantly lower price. Next, market opportunity for the product is analyzed. Most of the demand for CFLs comes from the upper income bracket. The users from the lower income bracket use IL mainly because it is cheaper than CFLs. The major players in the CFL industry are FE, Philips and Osram. The suppliers of pirated CFLs may also be called major players since they serve, a great number of customers. CFLs can be bought from either a formal retail outlet, like Handyman, or in informal retail outlets as in the sidewalk. Since users from the lower income bracket are lower income are the ones who do not use CFLs because of their high price, the company had this part of the market the target market. The product is called e-Light. Based from the survey on how much the customers are willing to pay for CFLs , the company decides to offer 85 PhP as e-Light's introductory price. The company also plans of launching the product all over the Philippines with sets of promotion strategies. There will be retailers who will serve as outlets for the product. For retailers outside Luzon, the goods will be shipped, but for those within Luzon, the company's delivery van will distribute the goods. Knowing that there is a sizable demand for the product, the project is concluded feasible, marketwise. To determine whether the product is technically feasible, the Technical Study follows. The group decided to manufacture 11-watt and 25-watt lamps. Both can either be encapsulated or bare. It is decided that all the parts of the product are to be outsourced except for the tubes, which will be manufactured by the company. The reason is to be able the company to recycle discharged tubes and use them as tube for the 11-watt lam. The outsourced parts will come from local suppliers. The raw materials for the making of the tube, since they are locally unavailable, will be imported. Most of the machines for the manufacturing of tubes are also imported. The projected capacity of the company steadily increases until it reaches the seventh year where its capacity until the tenth year is projected to be the same. In case the demand for e-Light does go up on year 7, it will only be during that time when the plans to increase its manpower level every year to compensate its increasing production. The plant will be located at Laguna Technopark Incorporated. With the integration of the results of the technical studies, it can be drawn into conclusion that the product is technically sound. To investigate if the company brings a rate of return, which satisfies both the proponent and the investor, and if the company is able to service its debts, the Financial Study is discuss next. Since the company is capital intensive, it has be a corporation. So, as its source of financing, shares of stocks will be sold to the public at PhP 1.00 par value for the first year. Another source of financing will be from a bank loan. From the Pro Forma Income statements, the company is found to be losing for its first three years, but on the next years the company already generates income. Different tests were performed to determine the liquidity, debt-service, operating efficiency, total debt-coverage, financial coverage and capital investment of the company. From these different tests of financial analyses, the project is concluded to be financially feasible. To establish the attractiveness of the company to the society and the economy, the benefits for the users is weighed against the cost of the company. The benefits are: decrease in cost of product, decrease in cost of power consumption, reduction of energy consumption, reduction of harmful gases emission, more job opportunities, utilization of local materials, better standard of living, and decrease in piracy. The costs involved are operating expenditure, capital investment and wastes. But the operating expenditures and the capital investment can be returned as profits based on the financial study. Also wastes can be managed so as not to harm the environment. So based on this reasoning it can be concluded that the benefits outweigh the costs, thus the project is socially and economically feasible. Over all, it is the conclusion of the study that the project is feasible.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management.
Keywords: e-light Company; Incandescent lamps; Participatory monitoring and evaluation (Project management)